Antibodies and Antibody Derivatives: New Partners in HIV Eradication Strategies - Carrillo, Jorge; Clotet, Bonaventura; Blanco, Julià (Frontiers in Immunology, 2018)
Promptly after primoinfection, HIV generates a pool of infected cells carrying transcriptionally silent integrated proviral DNA, the HIV-1 reservoir. These cells are not cleared by combined antiretroviral therapy (cART), and persist lifelong in treated HIV-infected individuals. Defining clinical strategies to eradicate the HIV reservoir and cure HIV-infected individuals is a major research field that requires a deep understanding of the mechanisms of seeding, maintenance and destruction of latently infected cells. Although CTL responses have been classically associated with the control of HIV replication, and hence with the size of HIV reservoir, broadly neutralizing antibodies (bNAbs) have emerged as new players in HIV cure strategies. Several reasons support this potential role: i) over the last years a number of bNAbs with high potency and ability to cope with the extreme variability of HIV have been identified; ii) antibodies not only block HIV replication but mediate effector functions that may contribute to the removal of infected cells and to boost immune responses against HIV; iii) a series of new technologies have allowed for the in vitro design of improved antibodies with increased antiviral and effector functions. Recent studies in non-human primate models and in HIV-infected individuals have shown that treatment with recombinant bNAbs isolated from HIV-infected individuals is safe and may have a beneficial effect both on the seeding of the HIV reservoir and on the inhibition of HIV replication. These promising data and the development of antibody technology have paved the way for treating HIV infection with engineered monoclonal antibodies with high potency of neutralization, wide coverage of HIV diversity, extended plasma half-life in vivo and improved effector functions. The exciting effects of these newly designed antibodies in vivo, either alone or in combination with other cure strategies (latency reversing agents or therapeutic vaccines), open a new hope in HIV eradication.